(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The security problem is an area that includes both aspects of political science and international relations and geopolitics. The article widely reveals the concept of security and determined the basic approaches and methods for the study of this phenomenon. Authors give specific examples from the history of mankind, certain stages of which are directly connected with the problem of security of any states or actors in international relations. They were also highlighted the concept of idealism, political realism and neorealism, models of which have access to the practice in order to ensure the effective functioning of political systems at the global level. Based on the theoretical positions the authors examine the current understanding of security and identify applied methods for studying this phenomenon in the dynamically developing geopolitical trends. Key words: security, international relations, geopolitics, security, political realism, political neorealism